The Effect of Training Through the Telegram Social Network on Osteoporosis-preventive Behaviour of Women - Zohreh Karimiankakolaki; Maryam Khadibi; Seyed Hossein Mousavi; Fatemeh Heidari (Galenos Yayinevi, 2020)
Objective:Osteoporosis is the most prevalent metabolic bone disease, and women are the most important group at risk. The present study was conducted to determine the effect of training through the Telegram social network on the osteoporosis-preventive behaviour (OPB) of women.Materials and Methods:This educational intervention study had a pre- and post-test design with a randomised control group. It was conducted on 60 women who referred to the health centres in Yazd suburbs. The women were randomly selected and assigned to the intervention and control groups. After filling out the questionnaires, the training messages package was sent to the intervention group via the Telegram group. One month later, the questionnaires were completed again, and the data were analysed using SPSS 18.0 and a paired and independent t-test.Results:The mean age of the participants was 30.20±5.34 years. The paired t-test was used to compare the mean scores of OPB in both groups before and after the training. The results showed that the difference in the mean scores in the intervention group (p=0.00) was significant compared with the control group, which was insignificant (p=0.054). Independent t-test results revealed that the mean behaviour score after training in the intervention group was higher than in the control group (p=0.00) and daily exercise behaviour had the highest mean increase.Conclusion:Training through the virtual space of Telegram concerning osteoporosis is effective in preventing osteoporosis, and a daily exercise behavioural regimen has the highest increase compared with other preventive behaviours.